1998
DOI: 10.1152/ajpregu.1998.275.1.r269
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-6 and TNF in thermoregulation and survival during sepsis in mice

Abstract: Interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) have been implicated as key mediators in inflammation, morbidity, and mortality associated with sepsis. We examined the role of IL-6 and TNF-α signaling on hypothermia, fever, cachexia, anorexia, and survival during sepsis induced by cecal ligation and puncture (CLP) in male and female gene knockout mice. Male wild-type mice developed an initial hypothermia and subsequent fever during sepsis. Male IL-6 knockout mice did not develop fever; rather, they ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
136
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 31 publications
14
136
0
Order By: Relevance
“…Our finding are consistent with the observation that IL-6 and TNF-␣ promote post-infection hypothermia in mice (46,47) but are at odds with the findings that IL-10 attenuates the hypothermic response to infection and inhibits LPS-induced production of TNF-␣ and IL-6 (48) and that IL-10 Ϫ/Ϫ mice exhibit more profound hypothermia than IL-10 ϩ/ϩ mice after LPS injection (49), Although our studies have not identified the molecular mechanisms responsible for the more profound hypothermia and systemic inflammation observed in GV Ϫ/Ϫ mice after lung infection with E. coli, they do show that an isolated increase in E. coli in lung parenchyma is sufficient to drive a systemic inflammatory response in these mice, because levels of E. coli in other organs, including liver, spleen, and kidneys as well as arterial blood are similar in GV ϩ/ϩ and GV Ϫ/Ϫ mice after pulmonary E. coli infection.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding are consistent with the observation that IL-6 and TNF-␣ promote post-infection hypothermia in mice (46,47) but are at odds with the findings that IL-10 attenuates the hypothermic response to infection and inhibits LPS-induced production of TNF-␣ and IL-6 (48) and that IL-10 Ϫ/Ϫ mice exhibit more profound hypothermia than IL-10 ϩ/ϩ mice after LPS injection (49), Although our studies have not identified the molecular mechanisms responsible for the more profound hypothermia and systemic inflammation observed in GV Ϫ/Ϫ mice after lung infection with E. coli, they do show that an isolated increase in E. coli in lung parenchyma is sufficient to drive a systemic inflammatory response in these mice, because levels of E. coli in other organs, including liver, spleen, and kidneys as well as arterial blood are similar in GV ϩ/ϩ and GV Ϫ/Ϫ mice after pulmonary E. coli infection.…”
Section: Discussionsupporting
confidence: 93%
“…IL-6 and IFN-␥ were released at significantly high amounts in the early phase after LPS injection both in WT and TG2 Ϫ/Ϫ mice. These molecules are responsible for the development of fever and cachexia (38), the symptoms of endotoxic shock observed initially also in TG2 animals. However, the levels of IL-6, IFN-␥, and G-CSF found at 24 h appear to discriminate between survivors and nonsurvivors, as follows: WT mice had significantly higher, and long lasting, proinflammatory cytokine levels when compared with TG2 Ϫ/Ϫ .…”
Section: Discussionmentioning
confidence: 95%
“…in macrophages. IL-6 and TNF-a have been considered the primary mediators of sepsis, 18 and a positive correlation has been found between multiple organ failure and serum levels of IL-6 and TNF-a. 19,20 Previously, blocking IL-6 was reported to improve the survival of mice in sepsis.…”
Section: Discussionmentioning
confidence: 99%